PNE, Meta 4 e sua implementação nos serviços de atendimento educacional especializado aos alunos das altas habilidades ou superdotação - Castro, Daniela dos Santos Borges (2022)
This research aimed to analyze how the National Education Plan, in its Goal 4, has been implemented in the Specialized Educational Services to students of High Abilities or giftedness in DF’s public schools, in an operating pole, along with teachers from this respective locus. We sought to contextualize the scenarios of the National Education Plan since its genesis and characterize the Specialized Educational Services, after an initial description of the public referred. The main theoretical references used were: Mantoan; Renzulli; Delou, among others. As for the methodological approach, the Qualitative research (Creswell) was adopted to, hence, from it, verify the effectiveness of the legislation pertaining to Specialized Educational Services to High Abilities/giftedness, and for its respective analysis followed the steps of Giorgi's Phenomenological Method, starting from a semi-structured interview with the purpose of gathering data from the carried out research. The research participants were four Specialized Educational Services professors. The results obtained from this research indicated that, in the comprehension of those involved, the legislation regarding care is large. However, it is not satisfactorily effective in the respective care services, as not all potential students with high skills/giftedness indicators are identified and referred to the Specialized Educational Service.